(untitled) (Nigerian Journal of Cooperative Economics and Management, 2021)
This study assessed the relationship between technology adoption and coconut production among Farmers in Mkpat-Enin LGA in Akwa-Ibom State, Nigeria. The study utilized primary data, which were collected through the use of copies of a structured questionnaire which was distributed to 384 small holder coconut farmers in the LGA. The study was anchored on Technology Acceptance Model (TAM). Descriptive statistics were used to present and discuss data, while a regression analysis model to test formulated hypotheses at the 5% level. The results of the study revealed that new positive relationships between adoption of new coconut seed varieties and coconut yield and between use of coconut extension services and coconut yield. The study recommends among others, that government should complement the efforts of the coconut growers in the procurement of not just high-yielding coconut seeds but also in the procurement of other coconut farm inputs such as organic manures and fertilizers, which literature has shown are also critical determinants of coconut output.